Предмет: Математика,
автор: taturl
5/6*(2,4х+6/35у)-1,2*(2/3х-5/7у)
Ответы
Автор ответа:
0
5/6 * (2,4х + 6/35у) - 1,2 * (2/3х - 5/7у) =
= 2х + 1/7у - 0,8х + 6/7у = (2х - 0,8х) + (1/7у + 6/7у) =
= 1,2х + у
Пояснения:
5/6 * 2,4х = (2,4 * 5 : 6)х = 2х
5/6 * 6/35у = 5/35у = 1/7у (дробь 5/35 сократили на 5)
-1,2 * 2/3х = -(1,2 * 2 : 3)х = -0,8х (-) * (+) = (-)
-1,2 * (-5/7)у = (1,2 * 5)/7у = 6/7у (-) * (-) = (+)
= 2х + 1/7у - 0,8х + 6/7у = (2х - 0,8х) + (1/7у + 6/7у) =
= 1,2х + у
Пояснения:
5/6 * 2,4х = (2,4 * 5 : 6)х = 2х
5/6 * 6/35у = 5/35у = 1/7у (дробь 5/35 сократили на 5)
-1,2 * 2/3х = -(1,2 * 2 : 3)х = -0,8х (-) * (+) = (-)
-1,2 * (-5/7)у = (1,2 * 5)/7у = 6/7у (-) * (-) = (+)
Автор ответа:
0
спасибо,я всё поняла,за пояснения отдельное спасибо,я очень благодарна!!!
Похожие вопросы
Предмет: Математика,
автор: adil3812
Предмет: Окружающий мир,
автор: mikitenkoveronika222
Предмет: Обществознание,
автор: YappyDoor
Предмет: Физика,
автор: Рита19962013